Sb2O3 nano array-carbon-based composite material as well as preparation method and application thereof
By performing seed crystal and hydrothermal reaction on carbon-based materials, Sb2O3 nanowire array-carbon-based composite materials with twin flower morphology were prepared, which solved the problems of insufficient performance and poor structural stability of existing lithium-ion battery negative electrode materials. , realizes the negative electrode material of high-performance lithium-ion batteries, and has excellent electrochemical performance and cycle stability.
Patent Information
- Application Number
- CN202411635214.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The graphite negative electrode material of existing lithium-ion batteries is theoretically smaller than that of capacity, making it difficult to meet the needs of high-performance lithium-ion batteries. At the same time, the Sb2O3 negative electrode material is prone to collapse due to volume expansion during charging and discharging, which limits its further development and application.
By performing seed crystal and hydrothermal reaction on carbon-based materials, Sb2O3 nanowire array-carbon-based composite materials with twin flower morphology were prepared, which achieved controllable synthesis of antimony oxides and improved the electrochemical performance of the material. .
The composite material has a high specific surface area, a large number of active sites and excellent discharge capacity. The discharge capacity of the first circle can reach 1900mAh/g, and has high cyclic stability and rate performance, which can effectively suppress the electrode material's Volume expansion.
Smart Images

Figure CN119503877A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a Sb 2 O 3 Nanoarray-carbon-based composite material and preparation method and application thereof. Background Art
[0002] In modern society where energy demand is increasing, lithium batteries can be seen everywhere in life, and they are often used in electronic products and new energy vehicles. In order to improve the service life of electronic products and automobiles, lithium batteries need to have good fast charging performance and cycle life. Among them, lithium-ion batteries (LiBs) have the advantages of high energy density, high average output voltage, superior cycle performance, fast charging and discharging, and long service life, and are called green batteries. As an important component of LiBs, negative electrode materials have an important influence on the energy density, cycle stability, safety, and amplification performance of lithium-ion batteries. However, the theoretical specific capacity of the currently commercially available graphite negative electrode materials is small, and its lithium storage performance is difficult to meet the needs of high-performance lithium-ion batteries. Therefore, the development of high-performance negative electrode materials is imminent.
[0003] Among various metal-based negative electrode materials, antimony oxide is considered to be the most promising energy storage electrode material due to its various advantages. It can be used as an electrode material for hybrid supercapacitors and has high energy density and power density. 2 O 3 Negative electrode materials are prone to structural collapse due to volume expansion during the charging and discharging process, which limits their further development and application. Summary of the invention
[0004] In view of the above technical problems, the present invention provides a Sb 2 O 3 Nanoarray-carbon-based composite material and preparation method and application thereof.
[0005] The technical solution adopted by the present invention is:
[0006] In one aspect, the present invention provides a Sb 2 O 3 The method for preparing the nano-array-carbon-based composite material comprises the following steps:
[0007] (1) soaking the carbon-based material in an antimony salt solution;
[0008] (2) annealing the soaked carbon-based material;
[0009] (3) The annealed carbon-based material is subjected to a hydrothermal reaction in an epitaxial growth solution to obtain Sb on the carbon-based material. 2 O 3Nanoarray; the epitaxial growth solution contains an antimony source, a template agent and a precipitant.
[0010] As a preferred embodiment, in step (1), the carbon-based material is selected from at least one of carbon fiber cloth, carbon paper, carbon cloth, carbon felt and mesh glassy carbon;
[0011] Preferably, the antimony salt solution is selected from at least one of an antimony acetate solution and an ethanol solution of ethylene glycol antimony;
[0012] Preferably, the concentration of the antimony salt solution is 0.005-0.02 mol / L;
[0013] Preferably, the soaking time is 24 to 48 hours.
[0014] As a preferred embodiment, in step (1), the carbon-based material is pretreated by acidification; the acidification is to heat the carbon-based material in an acid solution; the acid solution is selected from any one of a mixed solution of concentrated nitric acid, concentrated sulfuric acid and concentrated nitric acid; the heating temperature is 60 to 80° C.; the heating time is 2 to 4 hours;
[0015] Preferably, the carbon-based material is pre-treated by washing and drying before acidification;
[0016] Preferably, the carbon-based material further includes post-treatments of washing and drying after acidification; the drying is performed at 60 to 80° C. for 10 to 12 hours.
[0017] As a preferred embodiment, in step (2), the annealing temperature is 350-400° C.; the annealing time is 20-30 min;
[0018] Preferably, the heating rate of the annealing is 3-5°C / min;
[0019] In the technical solution of the present invention, annealing can cause the antimony-containing compound on the carbon-based material to lose water and transform into antimony oxide seed crystals, thereby completing the seeding operation.
[0020] As a preferred embodiment, in step (3), the antimony source is selected from SbCl 3 and at least one of potassium antimony tartrate;
[0021] Preferably, the template agent is polyvinyl alcohol; the molecular weight of the polyvinyl alcohol is 10000 to 70000;
[0022] Preferably, the precipitant is selected from at least one of hexamethylenetetramine, ammonia water and sodium hydroxide;
[0023] Preferably, the dosage ratio of the antimony source, template agent and precipitant is 0.8-1:0.4-0.5:1.
[0024] As a preferred embodiment, in step (3), the temperature of the hydrothermal reaction is 140 to 160° C.; and the time of the hydrothermal reaction is 14 to 16 hours.
[0025] In certain specific embodiments, step (3) further comprises post-treatment of washing and drying the carbon-based material after the hydrothermal reaction; the washing is washing with water and ethanol; the drying is drying at 60-80° C. for 10-12 hours.
[0026] In another aspect, the present invention provides Sb obtained by the above preparation method 2 O 3 Nanoarray-carbon-based composites.
[0027] In another aspect, the present invention provides the above-mentioned Sb 2 O 3 Application of nanoarray-carbon-based composite materials in the preparation of batteries;
[0028] Preferably, the invention is used in preparing negative electrode materials for lithium-ion batteries.
[0029] Compared with the prior art, the present invention has the following advantages:
[0030] The present invention obtains Sb with twin flower shape by in-situ preparation through seed crystal, hydrothermal reaction and the like. 2 O 3 Nanowire array-carbon-based composite material, which can be further applied to flexible electrode materials.
[0031] (1) The preparation method provided by the present invention realizes the controllable synthesis of antimony oxide and greatly improves the electrochemical performance of the material by controlling its morphology. 2 O 3 The nanowire array has a twin flower-shaped morphology structure, which can fully participate in the charge and discharge process of the battery. Due to its high specific surface area and large contact surface, it can provide more active sites for subsequent electrochemical reactions, thereby exposing more active materials to the electrolyte and reducing the diffusion path length of lithium, which helps to improve its utilization and rate performance. The composite material provided by the present invention not only has good activation performance and excellent discharge capacity, the first cycle discharge capacity can reach 1900mAh / g, and has high cycle stability and high cycle retention rate.
[0032] (2) Sb provided by the present invention 2 O 3 Nanowire array-carbon-based composites 2 O 3The composite of nanowire arrays and carbon-based materials not only greatly improves the conductivity of the material, but also inhibits the volume expansion of the electrode material and improves its electrochemical performance.
[0033] (3) Sb provided by the present invention 2 O 3 Nanowire array-carbon-based composite materials can be used as self-supporting flexible electrode materials. They can be directly used as electrode materials without the need for secondary treatment such as adhesive coating. The self-supporting substrate itself has good conductivity, which can effectively improve the electron transport of electrode materials with poor conductivity and promote the effective transport of carriers in the catalytic process. A strong interaction can be formed between the active material and the substrate, which can efficiently transport electrons and reduce the reaction barrier.
[0034] (4) The raw materials used in the present invention are easily available, low in cost, simple in preparation process, and easy to control, thus having high practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The Sb prepared in Example 1 of the present invention 2 O 3 SEM image of nanowire array-carbon matrix composite material.
[0036] Figure 2 The Sb prepared in Example 1 of the present invention 2 O 3 Cyclic stability diagram of nanowire array-carbon matrix composites.
[0037] Figure 3 The Sb prepared in Example 1 of the present invention 2 O 3 Rate performance diagram of nanowire array-carbon-based composites.
[0038] Figure 4 is Sb prepared in Example 2 of the present invention 2 O 3 SEM image of nanowire array-carbon matrix composite material. DETAILED DESCRIPTION
[0039] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0040] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0041] In the following examples, the M of polyvinyl alcohol is W It is 13000 to 23000.
[0042] Example 1
[0043] This embodiment provides a Sb 2 O 3 The preparation process of nanowire array-carbon-based composite material is as follows:
[0044] (1) Carbon cloth cleaning
[0045] The carbon cloth was cut into 3 cm*4 cm squares, and ultrasonically cleaned with acetone, water and ethanol for 15 min respectively. After cleaning, it was placed in a vacuum drying oven at 60 °C and dried for 12 h;
[0046] (2) Carbon cloth seed crystal
[0047] Place the cleaned and dried carbon cloth in a beaker containing 65% concentrated nitric acid and place in a 60°C water bath for 2 hours; rinse with deionized water and place in a vacuum drying oven at 60°C for 12 hours;
[0048] The dried carbon cloth was immersed in a 0.005 mol / L antimony acetate solution for 24 h, then placed in a muffle furnace, heated to 350 °C at a rate of 5 °C / min, and annealed for 30 min;
[0049] (3) Synthesis of Sb 2 O 3 Nanowire array-carbon-based composites
[0050] 0.6 g of polyvinyl alcohol (PVA) was added to 50 mL of deionized water, heated to 60°C until dissolved, and naturally cooled to room temperature; 1.2 g of hexamethylenetetramine and the carbon cloth seeded in step (2) were added, and stirred for 15 min; 1.14 g of SbCl 3 Continue stirring for 15 minutes;
[0051] The stirred solution and carbon cloth were transferred to a 100 mL reactor and placed in a vacuum drying oven at 140 °C for 14 h.
[0052] The carbon cloth after the hydrothermal reaction was washed with deionized water and anhydrous ethanol three times, and then placed in a vacuum drying oven at 60 ° C for 12 h to obtain Sb 2 O 3 Nanowire array-carbon-based composites.
[0053] Figure 1 The Sb prepared in this example is shown 2 O 3 SEM image of nanowire array-carbon-based composite material. It can be seen from the figure that the composite material has a nanoarray composed of nanowires that grow outward from the seed crystal nucleus point. The overall structure grows symmetrically and is named as a twin flower-shaped nanowire array structure.
[0054] In this embodiment, the above Sb 2 O 3 The nanowire array-carbon-based composite material was prepared into a battery and the electrochemical performance was tested as follows: Sb 2 O 3 The nanowire array-carbon-based composite material was cut into pieces, and the active mass of 1.0 mg / cm was selected as the electrode sheet to assemble the CR2032 lithium-ion battery. The assembly order was: negative electrode shell, lithium sheet, diaphragm, electrolyte, electrode sheet, gasket and spring. Among them, the diaphragm was a polypropylene film; the electrolyte was 1 mol / L LiPF 6 Solution, the solvent is a mixed solution of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1. The assembly process is carried out in a glove box filled with argon, and the water oxygen value is ≤0.01ppm. This embodiment uses the blue electricity tester Land-2001B model to test the telephone performance of the above-mentioned battery. The current density set for the rate performance test is 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g, 4A / g, 5A / g, and runs 5 laps at these current densities respectively. The current density set for the long cycle performance test is 1A / g, and the test voltage range is 0.01~3V. Test results are shown in Figure 2-3 ,from Figure 2 It can be seen from the graph that the electrode material prepared in this embodiment has stable cycle performance, and after 100 cycles, it still maintains a specific capacity of 1800mAh / g, and the first cycle coulombic efficiency is as high as 92%, and the subsequent cycle coulombic efficiency is stable at around 100%. Figure 3 It can be seen that the electrode material prepared in this embodiment has good rate performance. During the change from a small current of 0.1A to a large current of 5A and then reduced to 0.1A, the capacity remains at about 2000mAh / g, which has good rate performance.
[0055] Example 2
[0056] This embodiment provides a Sb 2 O 3 The preparation process of nanowire array-carbon-based composite material is as follows:
[0057] (1) Carbon cloth cleaning
[0058] The carbon cloth was cut into 3 cm*4 cm squares, and ultrasonically cleaned with acetone, water and ethanol for 15 min respectively. After cleaning, it was placed in a vacuum drying oven at 60 °C and dried for 12 h;
[0059] (2) Carbon cloth seed crystal
[0060] Place the cleaned and dried carbon cloth in a beaker containing 65% concentrated nitric acid and place in a 60°C water bath for 2 hours; rinse with deionized water and place in a vacuum drying oven at 60°C for 12 hours;
[0061] The dried carbon cloth was immersed in a 0.005 mol / L antimony acetate solution for 24 h, then placed in a muffle furnace, heated to 400 °C at a rate of 5 °C / min, and annealed for 25 min;
[0062] (3) Synthesis of Sb 2 O 3 Nanowire array-carbon-based composites
[0063] 0.6 g of polyvinyl alcohol (PVA) was added to 50 mL of deionized water, heated to 60°C until dissolved, and naturally cooled to room temperature; 1.4 g of hexamethylenetetramine and the carbon cloth seeded in step (2) were added, and stirred for 15 min; 1.14 g of SbCl 3 Continue stirring for 15 minutes;
[0064] The stirred solution and carbon cloth were transferred to a 100 mL reactor and placed in a vacuum drying oven at 140 °C for 10 h.
[0065] The carbon cloth after the hydrothermal reaction was washed with deionized water and anhydrous ethanol three times, and then placed in a vacuum drying oven at 60 ° C for 12 h to obtain Sb 2 O 3 Nanowire array-carbon-based composites.
[0066] The SEM image of the composite material prepared in this example is shown in Figure 4 ,As can be seen from the figure, its growth is not perfect, presenting a symmetrical butterfly shaped structure.
[0067] Example 3
[0068] This embodiment provides a Sb 2 O 3 The preparation process of nanowire array-carbon-based composite material is as follows:
[0069] (1) Carbon cloth cleaning
[0070] The carbon cloth was cut into 3 cm*4 cm squares, and ultrasonically cleaned with acetone, water and ethanol for 15 min respectively. After cleaning, it was placed in a vacuum drying oven at 60 °C and dried for 12 h;
[0071] (2) Carbon cloth seed crystal
[0072] Place the cleaned and dried carbon cloth in a beaker containing 65% concentrated nitric acid and place in a 60°C water bath for 2 hours; rinse with deionized water and place in a vacuum drying oven at 60°C for 12 hours;
[0073] The dried carbon cloth was immersed in a 0.005 mol / L antimony acetate solution for 24 h, then placed in a muffle furnace, heated to 350 °C at a rate of 5 °C / min, and annealed for 25 min;
[0074] (3) Synthesis of Sb 2 O 3 Nanowire array-carbon-based composites
[0075] 0.6 g of polyvinyl alcohol (PVA) was added to 50 mL of deionized water, heated to 60 °C until dissolved, and naturally cooled to room temperature; 1.3 g of hexamethylenetetramine and the carbon cloth seeded in step (2) were added, and stirred for 15 min; 1.14 g of SbCl 3 Continue stirring for 15 minutes;
[0076] The stirred solution and carbon cloth were transferred to a 100 mL reactor and placed in a vacuum drying oven at 140 °C for 16 h.
[0077] The carbon cloth after the hydrothermal reaction was washed with deionized water and anhydrous ethanol three times, and then placed in a vacuum drying oven and dried at 80 °C for 12 h to obtain Sb 2 O 3 Nanowire array-carbon-based composites.
[0078] The microstructure of the composite material prepared in this example does not change significantly compared with that in Example 1.
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Sb2O3 nanoarray-carbon-based composite material, characterized in that: The following steps are involved: (1) soaking the carbon-based material in an antimony salt solution; (2) annealing the soaked carbon-based material; (3) subjecting the annealed carbon-based material to a hydrothermal reaction in an epitaxial growth solution to obtain a Sb2O3 nanoarray on the carbon-based material; the epitaxial growth solution contains an antimony source, a template agent, and a precipitant.
2. The preparation method according to claim 1, characterized in that: In step (1), the carbon-based material is selected from at least one of carbon fiber cloth, carbon paper, carbon cloth, carbon felt and mesh glassy carbon; Preferably, the antimony salt solution is selected from at least one of an antimony acetate solution and an ethanol solution of ethylene glycol antimony; Preferably, the concentration of the antimony salt solution is 0.005-0.02 mol / L; Preferably, the soaking time is 24 to 48 hours.
3. The preparation method according to claim 1, characterized in that: In step (1), the carbon-based material is pretreated by acidification; the acidification is to heat the carbon-based material in an acid solution; the acid solution is selected from any one of a mixed solution of concentrated nitric acid, concentrated sulfuric acid and concentrated nitric acid; the heating temperature is 60 to 80° C.; the heating time is 2 to 4 hours; Preferably, the carbon-based material is pre-treated by washing and drying before acidification; Preferably, the carbon-based material further includes post-treatments of washing and drying after acidification; the drying is performed at 60 to 80° C. for 10 to 12 hours.
4. The preparation method according to claim 1, characterized in that: In step (2), the annealing temperature is 350-400° C. and the annealing time is 20-30 min. Preferably, the heating rate of the annealing is 3-5°C / min.
5. The preparation method according to claim 1, characterized in that: In step (3), the antimony source is selected from at least one of SbCl3 and potassium antimony tartrate; Preferably, the template is polyvinyl alcohol; the molecular weight of the polyvinyl alcohol is 30000-70000; Preferably, the precipitant is selected from at least one of hexamethylenetetramine, aqueous ammonia and sodium hydroxide.
6. The preparation method according to claim 1, characterized in that: In step (3), the dosage ratio of the antimony source, template agent and precipitant is 0.8-1:0.4-0.5:
1.
7. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the hydrothermal reaction is 140 to 160° C.; and the time of the hydrothermal reaction is 14 to 16 hours.
8. The preparation method according to claim 1, characterized in that: Step (3) also includes post-treatment of washing and drying the carbon-based material after the hydrothermal reaction; the washing is washing with water and ethanol; the drying is drying at 60 to 80° C. for 10 to 12 hours.
9. The Sb2O3 nanoarray-carbon-based composite material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the Sb2O3 nanoarray-carbon-based composite material according to claim 9 in preparing a battery; Preferably, the invention is used in preparing negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of antimony oxide composite carbon cloth sodium ion battery anode material
CN106784663A
Sodion cell negative electrode material C / Sb2O3 / C composite hollow sphere material preparation method and application thereof
CN108336337A
Method for preparing Sb2O3 / carbon felt flexible sodium ion battery anode material
CN110190246A
Antimony oxide / nitrogen doped graphene composite material, and preparation method and application thereof
CN110190256A
Preparation method of Sb2O5 / GO / carbon cloth electrode material for negative electrode of carbon cloth-based flexible sodium ion battery
CN110212165A